Prevalence of Needlestick Injuries and the preventive response of affected Dental healthcare persons working in Islamabad, Rawalpindi, and Abbottabad Pakistan. - Muhammad Umair; Abdul Manan; Sadia Rashid; Abdul Qadir; Nusrat Tariq; Akif Mahmud (Journal of University Medical & Dental College, 2024)
BACKGROUND AND OBJECTIVES: Needle sticks and other sharps injuries are common and serious hazards in healthcare facilities, exposing healthcare workers to blood-borne pathogens like HIV, hepatitis B, and C and affecting the physical and psychological health of dental staff. Our study aims to find the prevalence of needle injuries and preventive responses by affected ones.METHODOLOGY: A cross-sectional study was conducted at various Dental hospitals and clinics in Islamabad, Rawalpindi, and Abbottabad Pakistan, from December 2023 to May 2024. A close-ended questionnaire was distributed among 400 dentists and other healthcare workers at participating dental hospitals and clinics to collect the data. A total of 345 completely filled forms were collected and assessed by using SPSS 22.RESULTS: Out of 345, 241 healthcare persons reported needle injury at least once. The majority of injuries (78%) occurred at the chairside, 14% in the operation theatre and 8% at other locations. 197(81.7%) were self-inflicted during needle uncapping/recapping, and 44 (18.3%) were by the assisting staff. About 82% of injuries were with syringes while 18% were by sutures or other sharps. To manage the Needlestick injury (NSI), 159(66%) immediately washed the injury site with water and soap, 27(11%) pressed to bleed, 19(8%) applied antiseptic, 17(7%) took post-exposure prophylaxis against Hepatitis B, C and HIV/AIDS and 8 % did nothing.CONCLUSION: This study showed that Needlestick injury (NSI) was a common finding at dental workplaces, leaving a physical and psychological fear impact on healthcare persons.